Identification of Basalt Rock Distribution Using Resistivity Geoelectric Method in The National Capital City (IKN), Paser, East Kalimantan - Sopan, Langnanda Ekakurnia Putri; Agustin, Erisa; Kuncoro, Kirana Helga Aimee; Sarkowi, Muh; Kuswanto, Agus; Kumalasari, Isti Nur; Mulyasari, Rahmi (BRIN Publishing, 2024)
The construction of the National Capital City (IKN) is currently being carried out in East Kalimantan, resulting in increased demand for construction materials. Basalt is among the rocks that can be used as construction material in IKN. This rock has a high economic value due to its high demand but limited quantity. Basalt exploration around IKN is carried out to acquire rock resources and reduce construction costs due to its proximity to the site. This study aims to determine the distribution of basalt in the Kuaro area, East Kalimantan. The geology of the research area is composed of the Ultramafic Complex Formation, which comprises gabbro, basalt, serpentinite, and harzburgite. This research uses the Wenner-Alpha configuration geoelectric method to identify the distribution of basalt in the subsurface. Geoelectric measurements were carried out on six measurement lines, each line length of 470 m and electrode spacing of 10 m. The results of geoelectric data analysis show that the basalt has a specific resistivity value ranging from 200–4022 Ωm. Basalts were identified at depths of 10–75 m with 145 m, 325 m, 165 m and 183 m thicknesses in lines 1, 2, 5 and 6, respectively. The presence of basalt in lines 3 and 4 is at a depth of 10–75 m with an average thickness of 153 m and 125 m, respectively. Economically, basalt rocks in this area are classified as medium to highly recommendable for exploitation.